Physiology of sports (Results and Analysis) - Abduvaliyev Xurshid Abdulxayitovich (Zien Journals, 2022)
The system laws of a person’s organism adaptation determine the principles of the training level transfer from the training exercises to competitive ones and define the choice of the way of the training process organization
Keywords: effectiveness of sportsmen’s training; the laws of adaptation; theory and methodology of sport